Nanopartículas magnéticas para aplicaciones en tratamientos oncológicos de hipertermia (2020)
The present investigation focused on studying the applications of four magnetic structures - called YMNPs - in hyperthermia treatments. These treatments are gaining more and more ground within medical physics, since, on the one hand, their potential as a catalyst for conventional treatments (such as radiotherapy) has been demonstrated and, on the other hand, advances in the synthesis of NPs increasingly facilitate their industrial implementation. Specifically, the present study consisted of finding the geometric parameters for which the YMNPs maximize the heat dissipated per cycle (SPL) in the presence of an external magnetic field. In view of recent research, it was decided to study the YMNPs above the superparamagnetic limit. From a series of implementations in the Ubermag framework, it was found that most YMNPs maximize their SPL, above this region, when their diameter is between 20-25nm. Furthermore, it was concluded that within the YMNPs the core-shell structure stands out, which is capable of generating an SPL almost an order of magnitude higher than the other structures studied.